John’s Stone: A possible fragment of the 1908 Tunguska meteorite; Icarus; Vol. 243 - Anfinogenov J. John; Budaeva L. Larisa; Kuznetsov D. Yu. Dmitriy Yurievich; Anfinogenova Ya. J. Yana Jonovna (2014, 2014)
Title screen